Mobbing and Social Network Analysis - Tekşen, Kerem; Cemaloğlu, Necati (Technium Social Sciences Journal, 2023)
The aim of this research is to find out the level of mobbing experience of teachers working in educational institutions and to determine the network characteristics of both the social networks of the organizations where mobbing behavior is common and the participants in these networks. The target population of the research consists of teachers working in a province in Türkiye. The sample of the population was determined by cluster sampling method. In total, 376 teachers in 30 schools were reached, but 11 questionnaires were removed during the pre-analysis data scanning phase, and the remaining 365 questionnaires were analyzed. “Negative Acts Questionnaire” and “Social Network Analysis Questionnaire” were used as data collection tools in the research. SPSS 21.0 and UCINET 6 statistical package programs were used for the analysis of the data obtained in the research, and "frequency", "mean" and "multi-network measurements" were used in data analysis. As a result of the research, it is determined that the average level of mobbing experience of teachers in the organizations participating in the research is low. In addition, three organizations where mobbing is common is determined and the social network structures of these organizations is examined. It is observed that the average degrees and network densities are generally low in these organizations. In addition, these organizations generally show a low level of transitivity. In addition, it is evaluated that some of the participants in the social networks of these organizations may be victims of mobbing, considering that they have a low overall degree. As a support to this finding, it is observed that the participants in question have higher internal and external closeness, low betweenness and low eigenvector values compared to other participants in the organization.